2012
DOI: 10.1063/1.4709442
|View full text |Cite
|
Sign up to set email alerts
|

Surface enhanced fluorescence on three dimensional silver nanostructure substrate

Abstract: Multi-dimensional metallic nanostructures were fabricated by self-assembling silver nanoparticles on 3-aminopropyltrimethoxysilane-modified glass substrate and using p-aminothiophenol molecule as a linker. Surface enhanced fluorescence was investigated for Rhodamine 6G fluorophore molecules on the prepared 2D and 3D substrates. The experimental observation showed that the 3D nanostructured substrate presented stronger fluorescence enhancement, comparing with what was observed on the 2D nanoparticle arrays. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…As a result, many researches have been performed to study the fluorescence enhancement on such NP substrate, particularly the relationship between the orientation and distance of the fluorescent molecules, as well as the environment effect, with respect to the substrate [49][50][51]. Due to the coupling effect between the emission of the fluorophore and the SPR band of the SNP array nanostructure, the intensity of PEF influenced by adjusting the distributed characteristics of the nanopartices arrays was also observed experimentally [52].…”
Section: Pef From Nanoparticle Arrays Substratementioning
confidence: 99%
“…As a result, many researches have been performed to study the fluorescence enhancement on such NP substrate, particularly the relationship between the orientation and distance of the fluorescent molecules, as well as the environment effect, with respect to the substrate [49][50][51]. Due to the coupling effect between the emission of the fluorophore and the SPR band of the SNP array nanostructure, the intensity of PEF influenced by adjusting the distributed characteristics of the nanopartices arrays was also observed experimentally [52].…”
Section: Pef From Nanoparticle Arrays Substratementioning
confidence: 99%
“…. By comparing the peak at 558 nm from the prepared metal substrates with that from the reference substrate, we found that the greatest enhancement factor ( E f ) is about 8.4 based on the eqn : Ef=()IsampleIbackgroundtrue/()IreferenceIbackground where I sample is the fluorescence intensity of the Rh6G monolayer on the Ag/Au dendritic substrate, I reference is the fluorescence intensity of Rh6G monolayer on the clean glass substrate, and I background is the background intensity of the spectra.…”
Section: Resultsmentioning
confidence: 99%
“…This type of structure possesses a very strong local EM field and "hotspots" were easy to form. 22 Hence, the samples showed strong SERS effects.…”
Section: B Raman Spectroscopymentioning
confidence: 96%